Navigating Challenges in the Insurance Industry: A Comparative MCDM Analysis of Developed and Developing Countries - Gohar, Ali (Yugoslav Journal of Operations Research, 2024)
Insurance Policy adoption is the key to a better and safer living whether it comes to the individual or a business setup. Over the years this sector has been exposed to various challenges, especially when it comes to stability and gaining the trust of the people and organizations. The bigger struggle is the business hurdles this sector faces in a developing country and to do so, the current study was conducted to assess the attitude of Pakistani citizens toward insurance programs. Specifically, the study examines the reluctance of Pakistanis to purchase insurance policies as a means of protecting their savings. Due to the lesser available knowledge among the citizens, the reluctance towards the insurance policies is quite at a larger scale. To analyze this fact, MCDM techniques, i.e., TOPSIS and Decision Theory, have been implied to provide a means of assessing the efficiency of insurance companies and the reasons for their lagging in convincing the public to start changing their investment behavior. A comprehensive study of all Pakistani insurance companies has been conducted here. The data was obtained from the published financial statements of insurance companies, and the analysis of primary data was collected from two categories of people; employees and customers. The data enabled the current research to make a comparison between insurance in Pakistan and abroad to see how the two situations vary. According to the results, the companies abroad are more advanced in terms of means and facilities they provide in insurance, while in contrast, the lack of awareness and lesser trust in the companies leads to fewer insurance policies adoption in Pakistan.